The model for the end-stage liver disease and Child-Pugh score in predicting prognosis in patients with liver cirrhosis and esophageal variceal bleeding - Benedeto-Stojanov Daniela; Nagorni Aleksandar; Bjelaković Goran; Stojanov Dragan; Mladenović Bojan; Đenić Nebojša (Vojnosanitetski Pregled)
Background/Aim. Esophageal variceal bleeding is one of the most frequent and gravest complications of liver cirrhosis, directly life-threatening. By monitoring certain clinical and laboratory hepatocellular insufficiency parameters (Child-Pugh score), it is possible to determine prognosis in patients who are bleeding and evaluate further therapy. Recently, the Model for the End-Stage Liver Disease (MELD) has been proposed as a tool to predict mortality risk in cirrhotic patients. The aim of the study was to evaluate survival prognosis of cirrhotic patients by the MELD and Child-Pugh scores and to analyze the MELD score prognostic value in patients with both liver cirrhosis and variceal bleeding. Methods. We retrospectively evaluated the survival rate of a group of 100 cirrhotic patients of a median age of 57 years. The Child-Pugh score was calculated and the MELD score was computed according to the original formula for each patient. We also analyzed clinical and laboratory hepatocellular insufficiency parameters in order to examine their connection with a 15-month survival. The MELD values were correlated with the Child-Pugh scores. The Student's t-test was used for statistical analysis. Results. Twenty-two patients died within 15-months follow-up. Age and gender did not affect survival rate. The Child- Pugh and MELD scores, as well as ascites and encephalopathy significantly differed between the patients who survived and those who died (p < 0.0001). The International Normalized Ratio (INR) values, serum creatinine and bilirubin were significantly higher, and albumin significantly lower in the patients who died (p < 0.0001). The MELD score was significantly higher in the group of patients who died due to esophageal variceal bleeding (p < 0.0001). Conclusion. In cirrhotic patients the MELD score is an excellent survival predictor at least as well as the Child-Pugh score. Increase in the MELD score is associated with decrease in residual liver function. In the group of patients with liver cirrhosis and esophageal variceal bleeding, the MELD score identifies those with a higher intrahospital mortality risk.